EFFECT OF NURSERY BED SOIL DRENCHING WITH EMAMECTIN BENZOATE 1.9% WP, A NOVEL AVERMECTIN DERIVATIVE, TOWARDS ECO-FRIENDLY MANAGEMENT OF ROOT-KNOT NEMATODES IN CHILLI - AMIT KUMAR DAS; T. B. MAJI; V. KADAM; A. K. MUKHOPADHYAY (The Bioscan, 2014)
Three field experiments were carried out with the aim of detecting the efficacy of emamectin benzoate 1.9%WP as nematicide against root-knot nematodes and it shows that chilli seedlings treated at 2-3 leave stages in nursery bed with emamectin benzoate 1.9%WP @ 285.0g a.i./ha recorded highest reduction of Meloidogyne juveniles (J2 ) population (in soil) and female(f) nematode population(in per g of root) at every time of observation i.e. 35 days after sowing (DAS) [140.4(J2 ), 9.5(f)], 90 DAS [227.6(J2 )] and 180 DAS [251.9(J2 ), 16(f)] respectively. Similarly, the same dose of emamectin benzoate (@ 285.0g a.i./ha), when applied at 7 days before seed sowing (DBS) and 15 days before seed sowing in separate nursery bed also evidenced of recording lowest number of juveniles population in the soil and female RKN populations per g of root in the nursery or in the main field, at every occasion at 35 DAS [123.5(J2 ) and 10.0(f) in 7DBS, 135.0(J2 ) and 10.3(f) in 15DBS] and 180 DAS [249.0(J2 ) and 13.5(f) in 7DBS, 279.5(J2 ) and 16.5(f) in 15 DBS] respectively. None of the treatments exhibited visual signs of phytotoxic effect on chilli crop